2022
DOI: 10.1111/1759-7714.14286
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of EBUS‐TBNA under conscious sedation with meperidine and midazolam

Abstract: Background: According to the guidelines, endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) is the technique of choice for the diagnosis of mediastinal involvement in lung cancer; it is also useful for other mediastinal malignancies and benign pathology. Nevertheless, there is still discussion about whether to perform it under general anesthesia or under conscious sedation. Methods: We retrospectively analyzed the data of all patients who underwent EBUS-TBNA under conscious sedation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…For the higher sensitivity of TBNA in the diagnosis of lung cancer, totally the diagnosis sensitivity was 70.2% of male patients, and 62.9% of female patients. Previous studies also showed that there were little higher percent of males than females that underwent TBNA [19][20][21] . There was few study compared the diagnostic value of EBUS-TBNA between male and female patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…For the higher sensitivity of TBNA in the diagnosis of lung cancer, totally the diagnosis sensitivity was 70.2% of male patients, and 62.9% of female patients. Previous studies also showed that there were little higher percent of males than females that underwent TBNA [19][20][21] . There was few study compared the diagnostic value of EBUS-TBNA between male and female patients.…”
Section: Discussionmentioning
confidence: 96%
“…Anesthesia is very important to protect the patients to tolerate the operation of EBUS-TBNA [13,14,20] . In this study, the anesthesia method was mainly general intravenous anesthesia with spontaneous breathing, which was safe with little trauma of the patient and caused less adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in recent years report a comparable diagnostic yield of 55–99.5% in procedures performed under moderate sedation and a yield of 77.6–93% in procedures performed under general anesthesia. The incidence of adverse events in procedures performed under both modalities of periprocedural sedation is also similar [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].On the other hand, there have not been many studies comparing the diagnostic yield of RP-EBUS-TBNAs performed under general anesthesia versus moderate sedation.…”
Section: Discussionmentioning
confidence: 99%